The Prophet and the Thinker: The Quest for Paradise in the Pictorial and Religious Philosophy of A. A. Ivanov - Tsvetaeva, Marina N. (Actual Problems of Theory and History of Art, 2021)
The article is devoted to the biblical and evangelical theme in the works of A. A. Ivanov — an outstanding thinker of the historical genre, a painter-philosopher and prophet, who influenced the development of Russian and European art of the 19th–20th centuries; in particular, on Ge, Vrubel, Surikov, Nesterov, and Kandinsky. The testimonies of Nikolay Gogol, who notes the significance of the personal finding of Christ by Ivanov, is an important document for understanding his spiritual and aesthetic concept, the plots devoted to the image of the “miraculous” and the formation of a new pictorial and figurative language in such works as ‘The Archangel Gabriel strikes Zacharias dumb’ (1850), ‘The Annunciation to the Virgin Mary’, ‘The Dream of Joseph’, ‘Walking on the Waters’. Hence, his turn to comprehend Byzantine and Old Russian culture while working on sketches for the wall painting of the Church of the Resurrection of Christ in 1845 is quite natural. In the biblical and evangelical sketches, he used the effects of glowing, luminescence techniques, achieving the dematerialization of the classical form, its sculptureness, three-dimensionality, and volume. Thus, Ivanov’s historical works on the biblical and evangelical cycles went far beyond the limits of their time, lifting the viewer to the high order of moral and religious meaning of art, to deep reflection on the values of being, allowing them to enter a new artistic and ideological language.
Keywords: angelness; Byzantine art; heavenly world; Gogol; iconography; Kandinsky; psychology of image; prophecy; philosophy of color; Christian worldview; miraculous